Pengaruh Perencanaan Pajak, Kebijakan Dividen & Kepemilikan Institusional Terhadap Nilai Perusahaan - nurasmih Talhah (BJRM (Bongaya Journal of Research in Management), 2022)
This study aims to identify & analyze the impact of tax planning, dividend policy & corporate ownership on the business cost of manufacturing companies in the food and beverage sub-sector traded on the Indonesian Stock Exchange for the period of 2017. -2020. The data collection uses secondary data from financial reports available at www.idx.co.id and shares a total of 104 data for the period 2017-2020 of manufacturing companies in the Indonesian Stock Exchange-listed food and beverage sub-sector. observations. . The samples taken were 36 observations. The results of the study of data variables were tested against the classical hypothesis in the form of the normality hypothesis, the multicollinearity hypothesis and the heteroscedasticity hypothesis. The data analysis method uses multiple linear regression and hypothesis testing, after the data is collected, the data is analyzed using multiple linear regression and hypothesis testing, after the data is collected, the data is analyzed Use the Statistics Product and Service Solution (SPSS) version 21 program. The results of the survey show that the tax plan asa, measured by the effective tax rate (ETR), has a negative impact on corporate value with little impact. Dividend policies measured using the Dividend Payment Rate (DPR) have a significant positive impact on a company's value. Institusional Ownership (INST) has a positive impact on corporate value (PBV).